Choledochus blocked. Biliary regurgitation. Maximum acute biliary pressure. Passage threshold: clinical and experimental study - Cosco Montaldo, Homero; Liberman, Isaac (Cirugía del Uruguay, 2020)
Presented at session 6th August 1963